2003
DOI: 10.1111/j.1541-4329.2003.tb00027.x
|View full text |Cite
|
Sign up to set email alerts
|

An Immersion Approach to Teaching Food Science

Abstract: Introductory Food Science courses are most often lecture-based courses, but some include limited laboratory experiences. As described in this paper, the course minimizes lecture and maximizes experiential or "handson" learning by using an immersion approach to teach basic concepts of food science. Additionally, it requires students to work in groups to accomplish tasks, thus providing valuable experience in working cooperatively. The course has been taught in this basic manner at Ohio State for 10 y. Analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
(3 reference statements)
0
6
0
Order By: Relevance
“…Previous literature on immersion in the food and dining context indicates that various types of immersion can be attributed to purpose-driven outcomes. For instance, systems immersion [ 30 , 31 ] suggests increasing learning and understanding, while empathic [ 30 ] and social immersion [ 8 ] was found to trigger emotional responses in study participants. It thus seems that immersion can be achieved for educational and entertainment purposes as well, and is not reserved for creating esthetic and escapist experiences as illustrated in the experience economy framework [ 16 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous literature on immersion in the food and dining context indicates that various types of immersion can be attributed to purpose-driven outcomes. For instance, systems immersion [ 30 , 31 ] suggests increasing learning and understanding, while empathic [ 30 ] and social immersion [ 8 ] was found to trigger emotional responses in study participants. It thus seems that immersion can be achieved for educational and entertainment purposes as well, and is not reserved for creating esthetic and escapist experiences as illustrated in the experience economy framework [ 16 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…It thus seems that immersion can be achieved for educational and entertainment purposes as well, and is not reserved for creating esthetic and escapist experiences as illustrated in the experience economy framework [ 16 ]. Prior studies demonstrated that educational experiences can embody immersive characters which can enhance learning experiences [ 30 , 31 ]. Spatial immersion was revealed to be the most prominent form of immersion in the food and dining context and all studies confirmed that spatial immersion increased cognitive engagement during the experience consumption.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The published research that describes communication activities in food science classes is testimony to the importance food science faculty place on communication. In addition to the surveys conducted by food science faculty that monitor the extent of student frequency of use and preparedness of the communication outcomes found in the Success Skills (Clark and others ; Bohlscheid and Clark ), there are published accounts of communication activities designed by food science faculty in order for students to learn and practice these important skills (Boylston and Wang ; Duffrin ; Reitmeier and others ; Harper and others ; Barringer ; Hayes and Devitt ; Neal and others ; Corey and Firth ).…”
Section: Introductionmentioning
confidence: 99%
“…These include food chemistry and analysis, food safety and microbiology, food processing and engineering, applied food science, and so‐called “success skills.” The latter, which are deemed important for career accomplishment, have been formalized as communication skills, critical thinking skills, professionalism skills, life‐long learning skills, interaction skills, information acquisition skills, and organizational skills. In an effort to assist students in developing a number of these skills, active learning strategies involving group work and oral presentations have been implemented in food science courses (Reitmeier 2002; Boylston and Wang 2003; Harper and others 2003; Reitmeier and others 2004; Dykes 2009). These studies have produced favorable learning outcomes; however, the evaluation methods were different in each study and to that of other disciplines, thereby limiting comparisons to be drawn.…”
Section: Introductionmentioning
confidence: 99%